A CASE OF PRECURSOR B-ACUTE LYMPHOBLASTIC LEUKAEMIA MASQUERADING AS HYPEREOSINOPHILIA AND SPACE OCCUPYING LESION IN A 14-YEAR-OLD BOY - Sharif, Fatima; Junaid, Ayesha; Ashraf, Khadija (Journal of Ayub Medical College Abbottabad, 2022)
Peripheral blood eosinophilia is associated with a variety of benign and neoplastic conditions. Rarely, marked eosinophilia can mask an underlying Acute Leukaemia, delaying the correct diagnosis and treatment. Here, we report a case of 14-year-old boy, who presented with marked eosinophilia and space occupying lesion in the brain. Bone marrow biopsy and biopsy of brain lesion were performed to assess the underlying disorder, revealing the unexpected diagnosis of Precursor B- Acute Lymphoblastic Leukaemia in this patient. Cytogenetic studies revealed a normal male karyotype. This case highlights the significance of considering the rare possibility of Acute Lymphoblastic Leukaemia among the differential diagnosis of persistent eosinophilia in order to facilitate prompt and appropriate treatment.